A case of acute acquired obstructive hydrocephalus in a cat with suspected ischaemic cerebellar infarct. Issue 1 (April 2017) - Raimondi, Francesca; Lourinho, Filipa; Scott, Harry; Shihab, Nadia
Case summary: A case of acquired acute obstructive hydrocephalus that developed as a complication of an ischaemic infarct in the vascular territory of the rostral cerebellar artery is described in an adult domestic shorthair cat. The clinical findings, diagnostic investigations, treatment and prognosis are reported. MRI findings are described in detail. Relevance and novel information: This is the first report of obstructive hydrocephalus as a complication of an ischaemic infarct in the region of the rostral cerebellar artery in a cat. MRI findings are described in detail with regard to the recognition of the early signs of obstructive hydrocephalus. A brief review of the literature is included, as this complication has been frequently reported in humans.